Pola Kerja Sama antara Perusahaan Telepon Selular dan Pemasok Material dengan Mempertimbangkan Product Life Cycle - Bisma Jatmika Tisnasasmita; Wufron Wufron (Fakultas Ekonomi Universitas Garut, 2019)
An innovation product is known to have a relatively shorter lifecycle compared to a functional product. Innovations made by manufacturers accelerate the obsolescence of innovative products, so producers need to work together with their suppliers with flexible patterns. Suppliers always achieve efficiency and minimize the risk of unsold inventory, while innovative mobile phone manufacturers are constantly releasing new products. Flexible cooperation that can be implemented is non-equity and leads to joint collaboration, so that suppliers and cellphone companies can jointly maintain business continuity. Communication and participation are the keys to the success of this collaboration. This article provides a framework that shows the relationship between the product lifecycle and the pattern of cooperation between suppliers and cellphone manufacturers that can be developed into further research.